2020
DOI: 10.1101/2020.11.17.386508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hundreds of nuclear and plastid loci yield insights into orchid relationships

Abstract: Premise of the studyEvolutionary relationships in the species-rich Orchidaceae have historically relied on organellar DNA sequences and limited taxon sampling. Previous studies provided a robust plastid-maternal phylogenetic framework, from which multiple hypotheses on the drivers of orchid diversification have been derived. However, the extent to which the maternal evolutionary history of orchids is congruent with that of the nuclear genome has remained uninvestigated.MethodsWe inferred phylogenetic relations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…This latter method is capable of tackling challenges on phylogenetic reconstruction, such as incomplete lineage sorting and longbranch attraction. Since the premise of MSC is unlinked markers, it is mostly used for nuclear markers, although it might be used for organellar data, to evaluate conflict among genes (Pérez-Escobar et al, 2021;Zuntini et al, 2021). Although these two approaches are fundamentally different, they often result in similar topologies for data sets where the underlying signal is strong, as demonstrated by our results (see comparison in Appendix S6) and observed in others groups such as Apiaceae (Clarkson et al, 2021), Myrtales (Maurin et al, 2021), Ochnaceae (Shah et al, 2021), and Sapindaceae (Buerki et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This latter method is capable of tackling challenges on phylogenetic reconstruction, such as incomplete lineage sorting and longbranch attraction. Since the premise of MSC is unlinked markers, it is mostly used for nuclear markers, although it might be used for organellar data, to evaluate conflict among genes (Pérez-Escobar et al, 2021;Zuntini et al, 2021). Although these two approaches are fundamentally different, they often result in similar topologies for data sets where the underlying signal is strong, as demonstrated by our results (see comparison in Appendix S6) and observed in others groups such as Apiaceae (Clarkson et al, 2021), Myrtales (Maurin et al, 2021), Ochnaceae (Shah et al, 2021), and Sapindaceae (Buerki et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Much like a “next generation” rbcL , which underpinned so many Sanger sequencing-based plant phylogenetic studies, the Angiosperms353 genes offer opportunities for continuous synthesis of HTS data across angiosperms. The foundational dataset presented here can be re-used or extended for tree of life research at almost any taxonomic scale (Johnson et al 2019; Larridon et al 2019; Van Andel et al 2019; Murphy et al 2020; Pérez-Escobar et al 2020; Shee et al 2020; Slimp et al 2020; Beck et al 2021). Secondly, this is the first phylogenetic project to gather novel HTS data across angiosperms with a stratified taxon sampling at the genus level.…”
Section: Discussionmentioning
confidence: 99%
“…More than a dozen studies utilising Angiosperms353 probes are already published (e.g. Larridon et al 2019; Howard et al 2020; Murphy et al 2020; Pérez-Escobar et al 2020; Shee et al 2020; Slimp et al 2020; McLay et al in press), and two journal special issues focused on the probe set are in preparation arising from a recent symposium (Lagomarsino and Jabaily 2020). The probe set has also been adopted by the Genomics for Australian Plants consortium (https://www.genomicsforaustralianplants.com/), which aims to sequence all Australian angiosperm genera, coordinating with the PAFTOL project to optimise collective taxonomic coverage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and arrangement of plastid genes, and the substitution rates they exhibit, are all relatively conserved, which made it easier to design primers and recover sequences than for nuclear markers, considering approaches available at the time (e.g., Ness et al, 2011). However, the plastid genome mostly behaves as a single nonrecombining linkage group (Doyle, 1992;Ness et al, 2011), and so all genes within it could be considered to represent the same evolutionary history (Ness et al, 2011;Johnson et al, 2019), which may conflict with the history suggested by nuclear loci (e.g., Johnson et al, 2019;Pérez-Escobar et al, 2021). High-throughput sequencing (HTS) approaches, such as target sequence capture and, in particular, Hyb-Seq (capture + skimming; Weitemier et al, 2014;Dodsworth et al, 2019) result in a wealth of molecular data (both nuclear and organellar) for phylogenetic inference, which could help to clarify relationships across the order, beyond what is possible with plastid markers alone.…”
mentioning
confidence: 99%